Back Cover: Discovery and Characterization of ACT‐451840: an Antimalarial Drug with a Novel Mechanism of Action (ChemMedChem 18/2016). (13th September 2016) - Boss, Christoph; Aissaoui, Hamed; Amaral, Nathalie; Bauer, Aude; Bazire, Stephanie; Binkert, Christoph; Brun, Reto; Bürki, Cédric; Ciana, Claire‐Lise; Corminboeuf, Olivier; Delahaye, Stephane; Dollinger, Claire; et al.
Abstract : The back cover picture shows the successful collaboration between the Swiss TPH and Actelion Pharmaceuticals Ltd from the phenotypic screening hit via animal experiments to the antimalarial clinical candidate ACT‐451840, exhibiting a novel, yet unknown, mode of action. The quest for novel antimalarials has become urgent due to the first observed resistance developments against Artemisinin Combination Therapies (ACT). Extensive structure–activity investigation work ( P. falciparum NF54 and K1 and P. berghei ) and thorough in vivo pharmacokinetic and pharmacological characterization of several compounds were performed. In addition, discovery safety assessments and side‐effect potentials of key derivatives were evaluated. More information can be found in the Full Paper by Christoph Boss et al. onpage 1995 in Issue 18, 2016 (DOI:10.1002/cmdc.2016600298 ).